Peran Guru sebagai Motivator dalam Meningkatkan Prestasi dan Kemandirian Belajar Siswa Di MTs Miftahul Ulum Rengaspendawa - salamah, fiya fikrotus; Hanif, Mamun (Dahzain Nur, 2025)
A The role of the teacher as a motivator is one of the main keys in creating an effective and sustainable learning process, especially in the context of secondary level education such as at MTs Miftahul Ulum Rengaspendawa. Teachers not only act as deliverers of subject matter, but also as mentors who are able to generate enthusiasm, self-confidence, and students' desire to continue learning independently. Through a humanist and communicative approach, teachers encourage students to recognize their potential, set academic goals, and face learning challenges with a positive attitude. Motivation takes many forms, from rewarding students' efforts, providing constructive feedback, telling inspirational stories, to creating an inclusive and fun classroom atmosphere. These practices have a direct impact on improving student achievement, which is not only seen from academic grades, but also from active participation, initiative in completing tasks, and the ability to make decisions in the learning process. In addition, the motivational role of teachers has also proven effective in fostering learning independence, where students show a tendency to learn without high dependence on teacher guidance, and have a willingness to continue to develop. Therefore, the teacher as a motivator is not just a supporter, but an agent of change in shaping students' character. In an effort to comprehensively understand the influence of teachers' motivational roles on students, a mixed method approach that combines qualitative and quantitative methods is used.